IL-2/IL-2 Receptor Pathway Plays a Crucial Role in the Growth and Malignant Transformation of HTLV-1-Infected T Cells to Develop Adult T-Cell Leukemia - Maeda, Michiyuki; Tanabe-Shibuya, Junko; Miyazato, Paola; Masutani, Hiroshi; Yasunaga, Jun-ichirou; Usami, Kazumasa; Shimizu, Akira; Matsuoka, Masao (Frontiers in Microbiology, 2020)
T cells infected with human T-cell leukemia virus type 1 (HTLV-1) transform into malignant/leukemic cells and develop adult T-cell leukemia (ATL) after a long latency period. The tax (transactivator from the X-gene region) and HBZ (HTLV-1 bZIP factor) genes of HTLV-1 play crucial roles in the development of ATL. The process and mechanism by which HTLV-1-infected T cells acquire malignancy and develop ATL remain to be elucidated. Constitutive expression of Interleukin-2 (IL-2) receptor -chain (IL-2R/CD25), induced by the tax and HBZ genes of HTLV-1, on ATL cells implicates the involvement of IL-2/IL-2R pathway in the growth and development of ATL cells in vivo. However, the leukemic cells in the majority of ATL patients appeared unresponsive to IL-2, raising controversies on the role of this pathway for the growth of ATL cells in vivo. Here, we report the establishment of 32 IL-2-dependent T-cell lines infected with HTLV-1 from 26 ATL patients, including eight leukemic cell lines derived from 5 ATL patients, while no T-cell lines were established without IL-2. We have shown that the IL-2-dependent ATL cell lines evolved into IL-2-independent/-unresponsive growth phase, resembling ATL cells in vivo. Moreover, the IL-2-dependent non-leukemic T-cell lines infected with HTLV-1 acquired IL-2-independency and turned into tumor-producing cancer cells as with the ATL cell lines. HTLV-1-infected T cells in vivo could survive and proliferate depending on IL-2 that was produced in vivo by the HTLV-1-infected T cells of ATL patients and patients with HTLV-1-associated diseases and, acts as a physiological molecule to regulate T-cell growth. These results suggest that ATL cells develop among the HTLV-1-infected T cells growing dependently on IL-2 and that most of the circulating ATL cells progressed to become less responsive to IL-2, acquiring the ability to proliferate without IL-2.